Impact of aortic stenosis on layer-specific longitudinal strain: relationship with symptoms and outcome. (29th August 2019) - Ilardi, Federica; Marchetta, Stella; Martinez, Christophe; Sprynger, Muriel; Ancion, Arnaud; Manganaro, Roberta; Sugimoto, Tadafumi; Tsugu, Toshimitsu; Postolache, Adriana; Piette, Caroline; Cicenia, Marianna; Esposito, Giovanni; et al.
Abstract: Aims: The present study sought to assess the impact of aortic stenosis (AS) on myocardial function as assessed by layer-specific longitudinal strain (LS) and its relationship with symptoms and outcome. Methods and results: We compared 211 patients (56% males, mean age 73 ± 12 years) with severe AS and left ventricular ejection fraction (LVEF) ≥50% (114 symptomatic, 97 asymptomatic) with 50 controls matched for age and sex. LS was assessed from endocardium, mid-myocardium, and epicardium by 2D speckle-tracking echocardiography. Despite similar LVEF, multilayer strain values were significantly lower in symptomatic patients, compared to asymptomatic and controls [global LS: 17.9 ± 3.4 vs. 19.1 ± 3.1 vs. 20.7 ± 2.1%; endocardial LS: 20.1 ± 4.9 vs. 21.7 ± 4.2 vs. 23.4 ± 2.5%; epicardial LS: 15.8 ± 3.1 vs. 16.8 ± 2.8 vs. 18.3 ± 1.8%; P < 0.001 for all]. On multivariable logistic regression analysis, endocardial LS was independently associated to symptoms ( P = 0.012), together with indexed left atrial volume ( P = 0.006) and LV concentric remodelling ( P = 0.044). During a mean follow-up of 22 months, 33 patients died of a cardiovascular event. On multivariable Cox-regression analysis, age ( P = 0.029), brain natriuretic peptide values ( P = 0.003), LV mass index ( P = 0.0065), LV end-systolic volume ( P = 0.012), and endocardial LS ( P = 0.0057) emerged as independently associated with cardiovascular death. The best endocardial LS values associated with outcome was 20.6% (sensitivity 70%, specificity 52%, area under the curve = 0.626, P = 0.022). Endocardial LS (19.1 ± 3.3 vs. 20.7 ± 3.3, P = 0.02) but not epicardial LS (15.2 ± 2.8 vs. 15.9 ± 2.5, P = 0.104) also predicted the outcome in patients who were initially asymptomatic. Conclusion: In patients with severe AS, LS impairment involves all myocardial layers and is more prominent in the advanced phases of the disease, when the symptoms occur. In this setting, the endocardial LS is independently associated with symptoms and patient outcome.